Acute effect of whole-body vibration training on the roundhouse kick in Taekwondo athletes - Orellana Lepe, Gladys.; Warnier Medina, Alberto.; Olivares Fernández, Pedro.; Aguilar Gajardo, Sebastián.; Olivares Arancibia, Jorge Eduardo.; Yáñez Sepúlveda, Rodrigo. (Federación Española de Docentes de Educación Física, 2023)
Taekwondo is a combat sport with high physical demands, hence the search for new methods for its training is a relevant topic in sport science. The aim of this study was to identify the acute effect of whole-body vibrations on the kick frequency and Fatigue Index of the roundhouse kick in Taekwondo athletes. 10 Taekwondo athletes participated, all male (age: 21.1±1.52 years; body mass: 69.64±6.71 kg; bipedal height: 1.71±0.08 m; BMI: 23, 9±1,17). Each participant executed a control protocol and three training protocols on a vibrating platform. After each of the protocols, the FSKTmult was executed. The ANOVA test was used to compare the results between the groups and the Bonferroni post hoc test was applied, in addition, the effect size was calculated. There were significant differences between the control group and SV (p=0.018) in FSKT-2. In general, despite the above, a moderate effect was observed in FSKT-1 (n2= 0.070), FSKT-2 (n2= 0.128); FSKT-3 (n2= 0.070), FSKT-5 (n2= 0.070) and FSKT-Total (n2= 0.076). As for the protocols, all of them present moderate and high effects in the FSKTmult test, with the SD protocol being the one with the best results in effect size and, at the same time, one of those that demonstrates a lower KDI. The findings show that performing exercises with exposure to WBV generates an improvement in kicking frequency and KDI, evidencing the SD protocol a better relationship between performance and KDI.
Efecto agudo del entrenamiento con vibraciones de cuerpo completo sobre la patada circular en atletas de Taekwondo
Keywords: Efecto Agudo; FSKT; Taekwondo